2020
DOI: 10.1038/s41598-020-78308-z
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Mir-21 Mediates the Inhibitory Effect of Ang (1–7) on AngII-induced NLRP3 Inflammasome Activation by Targeting Spry1 in lung fibroblasts

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…37 A recent study also demonstrated that miR-21-5p targeting SPRY1 played a vital role in lung fibroblasts. 38 In this study, dual-luciferase assay results showed that miR-21-5p indeed directly targets SPRY1 in RAW 264.7 cells. The overexpression of SPRY1 enhanced the protective effect of the miR-21-5p inhibitor on inflammation responses.…”
Section: Discussionmentioning
confidence: 53%
“…37 A recent study also demonstrated that miR-21-5p targeting SPRY1 played a vital role in lung fibroblasts. 38 In this study, dual-luciferase assay results showed that miR-21-5p indeed directly targets SPRY1 in RAW 264.7 cells. The overexpression of SPRY1 enhanced the protective effect of the miR-21-5p inhibitor on inflammation responses.…”
Section: Discussionmentioning
confidence: 53%
“…ACE-2 down-regulation leads to an increased activation of NF-κB through the angiotensin receptor type 1 (AT1R) and mediated by protein kinases: mitogen-activated protein-kinase/extracellular signal axis-regulated-kinase (MAPK/ERK). This represents the mechanism of first-occurring NLR family pyrin domain containing 3 (NLRP3) inflammasome activation during SARS-CoV-2 infection [30,31].…”
Section: Sars-cov-2 Infection In Children and Immune Functionmentioning
confidence: 99%